MEMBACA KARAKTERISTIK DAN PETA GERAKAN AGRARIA INDONESIA - M Nazir Salim (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
In the beginning of the 21st century, agrarian movements in Indonesia began to rise and found its identity. The implementationof the Basic Agrarian Law (UUPA) has taken the dreams of the socialist and populist on their struggle for “a countrygooddeed”. UUPA firmly revised the Colonial Policy in Indonesian agrarian matters. Unfortunately, UUPA was buried by Suharto andreplaced by the Forestry Law 1967 as a way of “new tenuring system” on agrarian resources. Afterward, the New Order conductedcentralization and build bases of inequalities for the mastery of Indonesian agrarian structure. As a result, resistance of farmers,students, NGOs, and other groups emerged with a main issue to fight against the repressive policies of the New Order in theAgricultural field. After 1998, regime changes occurred over the history of the reversal of previous events, reclaiming occurrednearly throughout Indonesia. The character of the movement has changed. Farmers, NGOs, student and Scholar-Activist weredirectly involved in advocacies and movements. History tells that agrarian movements have extended through bureaucracies andpolitics (penetration policy and legislation) and the struggle in the Constitutional Court. This paper described a map of the New-Order-agrarian-regime reform and the reformation of the emerged movement characteristics by depicted some actors on the field.This paper used a comparison approach between movements during the new order regime and post-reformation era.Key words: movement characteristic, struggle, agrarian movement, New Order, Reformation.